2012
DOI: 10.1159/000335300
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments regarding Human Immunodeficiency Virus Infection and Stroke

Abstract: Human immunodeficiency virus (HIV) infection is strongly associated with ischemic stroke in the young. Data obtained from the Nationwide Inpatient Sample in the United States show an increase in the number of stroke hospitalizations in the HIV-infected population despite an overall decrease in the number of stroke hospitalizations. Few data exist, however, that address the mechanism of HIV-associated stroke. Recent studies have demonstrated that HIV may infect the endothelium and alter cerebrovascular function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 109 publications
(72 reference statements)
0
30
0
1
Order By: Relevance
“…In HIV-positive patients, the exact mechanisms whereby smoking increases the risk of cardiovascular events are yet to be determined, 21 but endothelial damage appears to be the cornerstone of heart disease in HIV 22 and it has become apparent that the effect of smoking can augment the damage produced by the virus itself, the immune response of the host, 23 or by potential toxicity of older drugs used in the treatment of HIV infection. 24 Furthermore, recent studies have shown that the population-attributable risk of death associated with smoking is higher (61.5%) among HIV-positive patients compared to controls (34.2%), postulating that in this particular category or patients, more life-years are lost to smoking than to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-positive patients, the exact mechanisms whereby smoking increases the risk of cardiovascular events are yet to be determined, 21 but endothelial damage appears to be the cornerstone of heart disease in HIV 22 and it has become apparent that the effect of smoking can augment the damage produced by the virus itself, the immune response of the host, 23 or by potential toxicity of older drugs used in the treatment of HIV infection. 24 Furthermore, recent studies have shown that the population-attributable risk of death associated with smoking is higher (61.5%) among HIV-positive patients compared to controls (34.2%), postulating that in this particular category or patients, more life-years are lost to smoking than to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration of large vessel atherosclerosis, endothelial injury and dyslipidemia can be caused by antiretroviral therapy [10]. FABP4 (fatty acid binding protein-4) is a strong plasma marker of metabolic disturbances in HIV-infected patients, and therefore, could serve to guide therapeutic intervention in this group of patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, патогенез ВИЧ-ассоциированной церебральной васкулопатии является многофактор-ным: вирусная инвазия стенки сосуда, эндотели-альное повреждение ВИЧ-протеинами, хроническая иммунная дисфункция и воспаление стенки сосудов, токсичность АРВТ, инфекционный (Varicella zoster) церебральный васкулит [22,32,[42][43][44][45].…”
Section: осложнения антиретровирусной терапииunclassified